PENGARUH PENERAPAN METODE TUTOR SEBAYA TERHADAP KEMAMPUAN BERHITUNG AWAL ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL V KOTA PEKANBARU - Rahayu Ningsih; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the results of field observations of the early numeracy skills of students and teachers were still using methods that are not varied. So that learning needs to be given in the form of peer tutoring methods. This study aimed to determine the effect of peer tutoring methods on early numeracy skills of children aged 5-6 years in kindergarten Aisyiyah Bustanul RA V Pekanbaru. The sample used in this study 11 children. The data collection techniques were used that observation. Data were analyzed using t-test. The study hypothesis is that there is a significant influence on early numeracy skills of students after applying the method of peer tutoring. It can be seen from the results also showed that the influence of the method of peer tutoring on numeracy skills early protégé is equal to (p) = 25.963 which may mean that numeracy skills early protégé influenced by the method of peer tutoring amounted to 25.963%, which is at the low category.Keywords: Early Numeracy, Peer Tutor